(3GdGYJHGQGJ GdSjGSjI ai eLdS GdGef hGKQgG Ydi GdeMceI GdLfGFjI GdOhdjI (B/ s - (3YHOGddg eMeO YHjO s; (3GMeO GHhGdhaG s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JfGhdJ gPg GdOQGSI(B: (3YdGbI eLdS GdGef HGdeMceI GdLfGFjI GdOhdjI(B: (3ai Xd GdGTcGdjI GdJGdjI(B: (3Gdi Gi eOi jecf ddGYJHGQGJ GdSjGSjI GdeJecfI ai JUQaGJ eLdS GdGef Gf JDKQ Ydi GSJbdGdjI GdeMceI GdLfGFjI GdOhdjI(B. (3hbO NdUJ GdOQGSI Gdi fJjLI eaGOgG hai Xd GdSdWGJ GdeefhMI ddeLdS JLGg GdeMceI GdLfGFjI GdOhdjI(B: (3habG ddfXGe GdGSGSi(B: (3Gf GdOhd GdcHQi OGFeI GdYVhjI ai GdeLdS hGdeSjWQI YedjG Ydjg(B: (3hef jOhQ eYgG hjQJHW HgG SJchf HefGi ef GdedGMbI GdbVGFjI GeGe GdeMceI GdLfGFjI GdOhdjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi , (B2009s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B361-379s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3GdGYJHGQGJ GdSjGSjI s; (3GdeMceI GdLfGFjI GdOhdjI s; (3eLdS GdGef s; (3eHOG JhGRi Gdbhis; (3TcdjI GdQbGHI Ydi GYeGd eLdS GdGefs; (3GKQ bQGQ eLdS GdGef HGdGMGdI deMceI GdYOd GdOhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs